1997
DOI: 10.1159/000119380
|View full text |Cite
|
Sign up to set email alerts
|

Differential Development of the Enhanced Metabolic Response during Amphetamine Sensitization

Abstract: Behavioral sensitization elicited by repeated administration of amphetamine does not fully develop until a period after discontinuation of amphetamine, but then persists undiminished for a long time. This experiment investigated the regional metabolic changes in rats pretreated with amphetamine and challenged after different abstinence periods (2, 7 and 28 days), using the 2-[14C]deoxyglucose method. The results demonstrated that chronic amphetamine administration enhanced rates of local cerebral gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…The decreased 2-DG uptake after haloperidol administration is thought to result from blockade of dopamine neurotransmission in the striatum [5,10]. This is supported by our previous studies of rats treated with long-term amphetamine, a dopaminergic stimulant [11,12]. In these studies, we found that several regions, especially the dopaminergic system, had elevated 2-DG uptake after long-term amphetamine administration.…”
Section: Discussionsupporting
confidence: 84%
“…The decreased 2-DG uptake after haloperidol administration is thought to result from blockade of dopamine neurotransmission in the striatum [5,10]. This is supported by our previous studies of rats treated with long-term amphetamine, a dopaminergic stimulant [11,12]. In these studies, we found that several regions, especially the dopaminergic system, had elevated 2-DG uptake after long-term amphetamine administration.…”
Section: Discussionsupporting
confidence: 84%
“…In another study, 2 d following 2 wk of daily 5 mg/kg d-Amph, rCMR glc was increased in one of 36 regions examined, within expectation by chance (Huang et al, 1997). Thus, the widespread depression of baseline k* for AA following 2.5 mg/kg daily d-Amph in our study (Figure 2) is very distinct from previous studies using rCMR glc measurements.…”
Section: Discussionsupporting
confidence: 56%
“…It has been shown that the stimulated dopamine release was enhanced in the striatal tissue slices of the AMPH-pretreated rats (Castaneda, Becker, & Robinson, 1988;Robinson & Becker, 1982). Thus, apparently a contextual input is not necessary to express the sensitization in the brain tissue in vitro, or even in the whole brain in vivo (see Huang et al, 1995Huang et al, , 1997. These results showed existence of a progressive neuroadaptation to AMPH treatment, but how this effect becomes connected to the CS and to the behavioral sensitization is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The development of sensitization and the testing included 3 stages (Huang et al, 1995(Huang et al, , 1997): In the pretreatment stage, rats were injected intraperitoneally with d-AMPH (1 mg/kg, Sigma Chemical, St. Louis, MO) or saline (control) daily for 2 weeks. Following each injection, rats were placed into one of the three contexts for 120 min before being returned to the home cage.…”
Section: Basic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation